Effects of Nitrogen and Phosphorus Limitation on Fatty Acid Contents in Aspergillus oryzae - Lv, Gongbo; Xu, Ying; Tu, Yayi; Cheng, Xiaojie; Zeng, Bin; Huang, Jianhua; He, Bin (Frontiers in Microbiology, 2021)
Aspergillus oryzae, commonly known as koji mold, has been widely used for the large-scale production of food products (sake, makgeolli, and soy sauce), and can accumulate a high level of lipids. In the present study, we showed the dynamic changes in A. oryzae mycelium growth and conidia formation under nitrogen and phosphorus nutrient stress. The fatty acid profile of A. oryzae was determinated and found that the content of unsaturated fatty acid was increased under nitrogen and phosphorus limitation. Transcriptomic analysis showed the expression profile of genes related to nitrogen metabolism, citrate cycle and linoleic acid synthesis, resulting in the accumulation of unsaturated fatty acid. qRT-PCR results further confirmed the reliability and availability of the differentially expressed genes obtained from the transcriptome analysis. Our study provides a global transcriptome characterization of the nitrogen and phosphorus nutrient stress adaptation process in A. oryzae. It also revealed that the mechanisms of A. oryzae in response to nitrogen and phosphorus stress. Our finding facilitates the construction of industrial strains with a nutrient-limited tolerance.